Contribuição da ciência cidadã para a conservação da avifauna tocantinense - Moura, Ricardo Silva (Universidade Federal do Tocantins, 2020)
The loss of biological diversity is one of the most severe environmental problems caused by humanity. Cataloging species is an activity that demands a lot from researchers, demands time, work and material costs. Conservation mechanisms require knowledge of the distribution and behavior of species, but even well-known groups such as birds can have their geographic limits poorly defined. In order to minimize cataloging problems and challenges for environmental conservation, Ciência Cidadã offers robust mechanisms to face these challenges. This study aims to analyze the contribution of citizen science to the conservation of regional avifauna. Of the 662 species of birds listed by Dornas 2009 and 2016, there was an addition of 3 species through the Citizen Science, totaling 665 species. Of these 558 (83.7%) are present in conservation units and 43 species (7.7%) correspond to unpublished records added by citizen science in conservation units. Bird watchers added 31 species to the list of protected birds in the UCPI and 85 in the UCUS, six of which are threatened species that were not on the list of the units' management plan. These platforms are essential to increase information and expand the range of scientific and informal research options, reinforcing the importance of Citizen Science for the dissemination of scientific knowledge and the dissemination of essential information, previously restricted only to professional researchers in their respective areas. However, as a recent approach, this tool still needs to be better disseminated, especially in developing countries.